2021
DOI: 10.1108/ecam-06-2021-0495
|View full text |Cite
|
Sign up to set email alerts
|

Public participation in infrastructure projects: an integrative review and prospects for the future research

Abstract: PurposeIn the past few decades, traditional project management theories mainly focused on quality, cost and schedule. However, with larger scale and wider influence of infrastructure projects, especially in megaprojects, social problems have gradually become pressing issues in the field of project governance. As the public is the main body of society, public participation has attracted the attention from both the academic field and industry field. Despite people are gradually realizing the significance of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…In addition, proper construction management (Ameyaw & Chan, 2015), regular communication, and progress monitoring (Kikwasi, 2021) can help administrate the construction process and avoid claims. Due to their unique characteristics, infrastructure projects are usually distinct from general building construction projects (Xiao & Hao, 2021). Therefore, discussing how to identify and manage defect claims in infrastructure projects is essential.…”
Section: Strategies To Manage Defect Claimsmentioning
confidence: 99%
“…In addition, proper construction management (Ameyaw & Chan, 2015), regular communication, and progress monitoring (Kikwasi, 2021) can help administrate the construction process and avoid claims. Due to their unique characteristics, infrastructure projects are usually distinct from general building construction projects (Xiao & Hao, 2021). Therefore, discussing how to identify and manage defect claims in infrastructure projects is essential.…”
Section: Strategies To Manage Defect Claimsmentioning
confidence: 99%
“…Furthermore, monthly meetings, look ahead programme, behavioural expectation cards, complains/queries database, contact photo sheet, notification of work bulletin and hand-outs are some of the tools used to communicate and provide project transparency (Collinge, 2016). Other common traditional communication tools are council newsletters and announcements, newspapers and radio, projects' websites, signage and traffic information boards and websites (Que et al., 2019), whereas modern methods include social media (Xiao and Hao, 2023).…”
Section: Key Literature Findings On Stakeholder Management Challenges...mentioning
confidence: 99%
“…Along these lines, the inclusion of the local community is also key to ensure that infrastructural projects actually serve the needs of their users (Xiao and Hao, 2021; Valdes-Vasquez and Klotz, 2013). Numerous studies have shown that urban planning that takes into account positive health outcomes reinforces the need to draw on local knowledge (D'Onofrio and Trusiani, 2018; Frumkin et al.…”
Section: Salutogenic Approach To Infrastructure Designmentioning
confidence: 99%